Efficacy of WHO recommendation for continued breastfeeding and maternal cART for prevention of perinatal and postnatal HIV transmission in Zambia. Issue 1 (1st July 2015) - Ngoma, Mary S; Misir, Amita; Mutale, Wilbroad; Rampakakis, Emmanuoil; Sampalis, John S; Elong, Angela; Chisele, Sam; Mwale, Abel; Mwansa, Jonathan K; Mumba, Scholastica; Chandwe, Mula; Pilon, Richard; et al.
Abstract : Introduction: To prevent mother‐to‐child transmission (MTCT) of HIV in developing countries, new World Health Organization (WHO) guidelines recommend maternal combination antiretroviral therapy (cART) during pregnancy, throughout breastfeeding for 1 year and then cessation of breastfeeding (COB). The efficacy of this approach during the first six months of exclusive breastfeeding has been demonstrated, but the efficacy of this approach beyond six months is not well documented. Methods: A prospective observational cohort study of 279 HIV‐positive mothers was started on zidovudine/3TC and lopinavir/ritonavir tablets between 14 and 30 weeks gestation and continued indefinitely thereafter. Women were encouraged to exclusively breastfeed for six months, complementary feed for the next six months and then cease breastfeeding between 12 and 13 months. Infants were followed for transmission to 18 months and for survival to 24 months. Text message reminders and stipends for food and transport were utilized to encourage adherence and follow‐up. Results: Total MTCT was 9 of 219 live born infants (4.1%; confidence interval (CI) 2.2–7.6%). All breastfeeding transmissions that could be timed (5/5) occurred after six months of age. All mothers who transmitted after six months had a six‐month plasma viral load >1, 000 copies/ml (p<0.001). Poor adherence to cART as noted by missed dispensary visits was associated with transmission (p=0.04). Infant mortality was lower after six months of age than during the first six months of life (p=0.02). The cumulative rate of infant HIV infection or death at 18 months was 29/226 (12.8% 95 CI: 7.5–20.8%). Conclusions: Maternal cART may limit MTCT of HIV to the UNAIDS target of <5% for eradication of paediatric HIV within the context of a clinical study, but poor adherence to cART and follow‐up can limit the benefit. Continued breastfeeding can prevent the rise in infant mortality after six months seen in previous studies, which encouraged early COB.